Pivotal Advance: Avian colony-stimulating factor 1 (CSF-1), interleukin-34 (IL-34), and CSF-1 receptor genes and gene products - FARES, MARIO ALI (My University, 2010)
Macrophages are involved in many aspects of development, host defense, pathology, and homeostasis. Their normal differentiation, proliferation, and survival are controlled by CSF-1 via the activation of the CSF-1R. A recently discovered cytokine, IL-34, was shown to bind the same receptor in humans. Chicken is a widely used model organism in developmental biology, but the factors that control avian myelopoiesis have not been identified previously. The CSF-1, IL-34, and CSF1R genes in chicken and zebra finch were identified from respective genomic/cDNA sequence resources. Comparative analysis of the avian CSF1R loci revealed likely orthologs of mammalian macrophage-specific promoters and enhancers, and the CSF1R gene is expressed in the developing chick embryo in a pattern consistent with macrophage-specific expression. Chicken CSF-1 and IL-34 were expressed in HEK293 cells and shown to elicit macrophage growth from chicken BM cells in culture. Comparative sequence and co-evolution analysis across all vertebrates suggests that the two ligands interact with distinct regions of the CSF1R. These studies demonstrate that there are two separate ligands for a functional CSF1R across all vertebrates.
PUBLISHED
Keywords: Chicken; zebra finch; macrophage; co-evolution